A case of Pyogenic Granuloma at an unusual location - Yugandar Inakanti; Akshaya Nagaraja; Srilakshmi Peddireddy; Vijayshankar Metikurke (Our Dermatology Online, 2014)
Pyogenic granulomas are common, acquired, benign vascular lesions of the skin and mucousmembranes that can develop both spontaneously and traumatically. Pyogenic Granuloma more commonly involves Gingiva (75% of all the cases). An extragingival occurrence of pyogenic granuloma is rare. We present an unique case of a male patient aged 24 years affected by Pyogenic Granuloma of urethral meatus. Although penile pyogenic granulomas have previously been observed over glans penis,prepuce and shaft of penis,there are no reports affecting meatus.